Linguistic expertise of conflict texts: a comparative analysis of invective speech acts in English, Russian and Uzbek - Baltayeva, Lamiya Baxtiyorovna (The Lingua Spectrum, 2026)
This article examines the linguistic and pragmatic characteristics of invective speech acts in English, Russian, and Uzbek conflict discourse. The study focuses on verbal aggression, offensive language, and evaluative expressions in professional and interpersonal communication. Through comparative linguistic analysis, the research identifies the semantic, pragmatic, and cultural mechanisms underlying conflict texts across the three languages. Particular attention is devoted to the distinction between insult and value judgment in multilingual discourse and to the role of linguistic expertise in determining legal qualification. The article demonstrates that English conflict communication frequently employs indirect evaluative strategies and subjective opinion markers, Russian discourse is characterized by explicit emotional expressiveness and invective intensification, while Uzbek conflict speech reflects culturally conditioned hierarchy, etiquette norms, and socially marked forms of humiliation. The study also analyzes a multilingual professional conflict scenario in which delayed reporting escalates into verbal aggression. The findings reveal that legal interpretation of offensive speech depends not only on lexical semantics but also on communicative context, cultural expectations, and pragmatic intention. The research contributes to pragmatics, comparative linguistics, discourse analysis, and forensic linguistic expertise in multilingual environments.